2016
DOI: 10.1038/nplants.2016.195
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Endogenous Arabidopsis messenger RNAs transported to distant tissues

Abstract: In the version of this Article originally published, the x-axis scale in Fig. 4b was incorrectly labelled and should have ranged from-10 to 10. This has been corrected in all versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Despite strong evidence in support of phloem-based movement, consistent evidence has shown that up to a quarter of identified mobile transcripts move against the source-to-sink gradient (from root to shoot in most cases). This observation conflicts with the assumption that the mRNA mobileome is transported via bulk phloem flow ( Ruiz-Medrano et al 1999 ; Notaguchi et al 2015 ; Yang et al 2015 ; Thieme et al 2016 ; Zhang et al 2016b ; Li et al 2021 ). These findings imply that mRNAs are likely moving against source-to-sink within the phloem, although no mechanism for this movement has been described ( Thieme et al 2015 ; Kehr and Kragler 2018 ).…”
Section: Molecular Superhighway: Mrna Transit Through the Phloemmentioning
confidence: 65%
See 2 more Smart Citations
“…Despite strong evidence in support of phloem-based movement, consistent evidence has shown that up to a quarter of identified mobile transcripts move against the source-to-sink gradient (from root to shoot in most cases). This observation conflicts with the assumption that the mRNA mobileome is transported via bulk phloem flow ( Ruiz-Medrano et al 1999 ; Notaguchi et al 2015 ; Yang et al 2015 ; Thieme et al 2016 ; Zhang et al 2016b ; Li et al 2021 ). These findings imply that mRNAs are likely moving against source-to-sink within the phloem, although no mechanism for this movement has been described ( Thieme et al 2015 ; Kehr and Kragler 2018 ).…”
Section: Molecular Superhighway: Mrna Transit Through the Phloemmentioning
confidence: 65%
“…Since this initial discovery, mRNAs have been found in the phloem sap of a broad range of families, including the Brassicaceae, Cucurbitaceae, and Euphorbiaceae ( Doering-Saad et al 2002 , 2006 ; Omid et al 2007 ; Deeken et al 2008 ; Kanehira et al 2010 ; Dinant and Kehr 2013 ; Ostendorp et al 2017 ). These observations of mRNA in the phloem sap have subsequently been expanded upon and now demonstrate that RNA movement is associated with diverse processes, including gene silencing, development, abiotic responses, and plant–parasite interactions ( Kim et al 2001 ; Haywood et al 2005 ; Banerjee et al 2006 ; David-Schwartz et al 2008 ; Molnar et al 2010 ; Melnyk et al 2011 ; Pallas and Gómez 2013 ; Kim et al 2014 ; Lewsey et al 2016 ; Thieme et al 2016 ; Ghate et al 2017 ; Shahid et al 2018 ; Johnson et al 2019 ). Indeed, across a wide range of studies, there is a ubiquitous presence of long-distance mobile RNAs moving throughout the plant body.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation